Buddhist Propagation in Modern Society: A Case Study of Monks in Northeastern Thailand - (Hanchaina), Phra Tawan Chotiyo; (Daosayam Klalod), Phrakhru Sri Phutthibandit; (Mit Wanyao) , Phrakhru Pariyattipatthanbandit (Dhammathas Academic Journal, 2025)
This research aims to 1) study the propagation of Buddhism as found in Buddhist scriptures; 2) study the dissemination of Buddhism in modern society; and 3) propose a model for the dissemination of Buddhism in modern society by the monastic community in Northeastern Thailand. The research is qualitative, using tools such as in-depth interviews and group discussions. Key informants include 5 monks, 5 religious scholars, 5 community leaders, 5 local sages, and 10 laypeople, totaling 30 participants. The data was analyzed descriptively. The research results are as follows: 1. The propagation of Buddhism as found in Buddhist scriptures involves teaching the Dhamma that the Buddha attained to liberate sentient beings from suffering. It began with the Buddha's first sermon to the Pañcavaggīya in the Deer Park at Isipatana. The Buddha initially sent 60 disciples to spread Buddhism with the goal of benefiting and bringing happiness to the masses, the principle and method used by the Buddha and his monastic disciples is to meet people and choose to teach them the Dharma that suits their temperament. 2. The dissemination of Buddhism in modern society has taken many forms, adapted by monks to suit contemporary needs and to provide options for those seeking to learn the Dhamma. Buddhism is disseminated through books, articles, sermons, teachings, Dhamma lectures, and through modern media such as television, YouTube, websites, as well as through social welfare activities like vocational training, reforestation, water source creation, peaceful community building, and the establishment of meditation centers. 3. The model for disseminating Buddhism in modern society by the monastic community in Northeastern Thailand proposed in this research includes four approaches: (1) Community development through the propagation of Buddhism, (2) Propagation of Buddhism through cultural traditions, (3) Buddhist communication dissemination, and (4) Propagation of Buddhism through charitable activities.